AB0953 A Comparison of Region-Based and Pixel-Based CEUS Kinetics Parameters in the Differentiation of Rheumatoid Arthritis and Simil-Rheumatoid Psoriatic Arthritis. (10th June 2014) - Raffeiner, B.; Grisan, E.; Bernardi, L.; Botsios, C.; Ometto, F.; Coran, A.; Beltrame, V.; Ciprian, L.; Punzi, L.; Stramare, R.
Abstract : Background: Contrast Enhanced Ultrasound (CEUS) examination of the small joints has emerged as a sensitive tool for assessing disease activity in arthritis (1). This evaluation bases on subjective semi-quantitative scales, that are able to capture the macroscopic degree of vascularization, but are unable to detect the subtler differences in kinetics perfusion parameters that might lead to a deeper understanding of disease pathogenesis (2, 3). Automated quantitative assessment is mostly performed by means of the Qontrast software package, that requires the user to define a region of interest, whose mean intensity curve is fitted with an exponential function. Objectives: To show that using a more physiologically motivated perfusion curve, by estimating the kinetics parameters separately pixel per pixel, is able to differentiate more effectively different vascularization patterns even in clinically identic forms such as rheumatoid (RA) and simil-rheumatoid psoriatic arthritis (srPsA). Methods: 64 outclinic patients with polyarthritis of hands, 32 with RA and 32 with srPsA, were recruited. The most active joint was chosen for CEUS examination using a US device (Mylab70, Esaote) equipped with Contrast tuned Imaging (CnTI, Esaote), and as contrast agent sulfur hexafluoride microbubbles (SonoVue; Bracco International). Both the anatomical B-mode image and the CnTI cineloop video were digitally stored for subsequent dedicated software analysis. The contrast time-activity curve of all pixels belonging to the synovial and perisynovial region was analyzed fitting a gamma curve f(t)=A(t-t0)a × e(t-t0)/b for RA and srPsA. Mathematical function for region-based and pixel-based parameters were calculated and compared between both diseases. Results: In addition to the parametric map of the synovial perfusion that can be obtained with a pixel-based analysis but not with a region-based, thus allowing the identification of the activity foci, the pixel-based mean parameters are more able to capture the different vascularization patterns, as result from the p-values between the two populations (RA vs srPsA), that are consistently lower for pixel-based derived parameters, especially for time to contrast appearance t0. Conclusions: We compared region-based and pixel-based quantitative analysis of contrast kinetics in CEUS, for the assessment of vascularization patterns in different types of arthritis. We showed that perfusion markers derived by pixel-based analysis provide stronger evidence of kinetic differences between RA and srPsA, even when no clinical differences are present. References: Klauser A. Eur Radiol 2005;15(12):2404-10. Klauser A. Ultraschall in Med 2011;31-7. Stramare R. J Clin Ultrasound 2012;40(3):147-54. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3748